Characterization of the murine macrophage response to infection with virulent and avirulent Burkholderia species. Issue 1 (December 2015) - Chiang, Chih-Yuan; Ulrich, Ricky; Ulrich, Melanie; Eaton, Brett; Ojeda, Jenifer; Lane, Douglas; Kota, Krishna; Kenny, Tara; Ladner, Jason; Dickson, Samuel; Kuehl, Kathleen; Raychaudhuri, Rahul; et al.
Abstract Background Burkholderia pseudomallei (Bp) andBurkholderia mallei (Bm) are Gram-negative facultative intracellular pathogens, which are the causative agents of melioidosis and glanders, respectively. Depending on the route of exposure, aerosol or transcutaneous, infection by Bp or Bm can result in an extensive range of disease – from acute to chronic, relapsing illness to fatal septicemia. Both diseases are associated with difficult diagnosis and high fatality rates. About ninety five percent of patients succumb to untreated septicemic infections and the fatality rate is 50 % even when standard antibiotic treatments are administered. Results The goal of this study is to profile murine macrophage-mediated phenotypic and molecular responses that are characteristic to a collection of Bp, Bm, Burkholderia thailandensis (Bt) andBurkholderia oklahomensis (Bo) strains obtained from humans, animals, environment and geographically diverse locations.Burkholderia spp. (N  = 21) were able to invade and replicate in macrophages, albeit to varying degrees. All Bp (N  = 9) and four Bm strains were able to induce actin polymerization on the bacterial surface following infection. Several Bp and Bm strains showed reduced ability to induce multinucleated giant cell (MNGC) formation, while Bo and Bp 776 were unable to induce this phenotype. Measurement of host cytokine responses revealed a statistically significant Bm mediated IL-6 and IL-10 production compared to Bp strains. Hierarchical clustering of transcriptional data from 84 mouse cytokines, chemokines and their corresponding receptors identified 29 host genes as indicators of differential responses between theBurkholderia spp. Further validation confirmed Bm mediatedIl-1b, Il-10, Tnfrsf1b andIl-36a mRNA expressions were significantly higher when compared to Bp and Bt. Conclusions These results characterize the phenotypic and immunological differences in the host innate response to pathogenic and avirulentBurkholderia strains and provide insight into the phenotypic alterations and molecular targets underlying host-Burkholderia interactions.